2008
DOI: 10.1097/sla.0b013e3181859f71
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Success of Limited Exploration for Primary Hyperparathyroidism Using Ultrasound, Sestamibi, and Intraoperative Parathyroid Hormone

Abstract: This is the largest study to evaluate the prevalence of additional parathyroid pathology in patients who are candidates for LE. Limitations in localizing studies and IOPTH fail to identify MGD in at least 16% of patients, risking future recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
100
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(110 citation statements)
references
References 21 publications
3
100
2
3
Order By: Relevance
“…Routine BNE was then performed in all these patients revealing 16% having additional enlarged parathyroid glands. The authors concluded that the long term failure or recurrence rate for targeted parathyroidectomy may be higher than reported in early results [47]. What remains unknown is whether or not these enlarged parathyroid glands found on BNE that are judged to be abnormal by the surgeon and may otherwise been left alone or never seen during targeted operations later become hyperfunctioning glands.…”
Section: Intraoperative Parathyroid Hormone Monitoringmentioning
confidence: 44%
See 1 more Smart Citation
“…Routine BNE was then performed in all these patients revealing 16% having additional enlarged parathyroid glands. The authors concluded that the long term failure or recurrence rate for targeted parathyroidectomy may be higher than reported in early results [47]. What remains unknown is whether or not these enlarged parathyroid glands found on BNE that are judged to be abnormal by the surgeon and may otherwise been left alone or never seen during targeted operations later become hyperfunctioning glands.…”
Section: Intraoperative Parathyroid Hormone Monitoringmentioning
confidence: 44%
“…MGD) leading to future disease recurrence. In one study of simulated targeted parathyroidectomy in 916 patients with primary hyperparathyroidism, preoperative sestamibi and ultrasound were used for parathyroid localization, and IPM was performed in all patients [47]. Routine BNE was then performed in all these patients revealing 16% having additional enlarged parathyroid glands.…”
Section: Intraoperative Parathyroid Hormone Monitoringmentioning
confidence: 99%
“…(Oltmann et al, 2011)) Siperstein et al showed that preoperative localizing studies and IOPTH failed to identify multiglandular disease in at least 16% of pHPT patients if routine BNE was employed in all patients. (Siperstein et al, 2008) This issue certainly raises concerns on whether by performing MIP and following the IOPTH criterion may lead to higher recurrences in the future. However, in many of the large (>1000 cases) series of image-guided MIP with IOPTH, it is reassuring to find that the long-term cure rate does not appear to be inferior to conventional BNE.…”
Section: Iopthmentioning
confidence: 99%
“…The assumption that minimally invasive parathyroid surgery has equivalent results to four gland exploration has recently been called into question by Norman et al [18] and by Siperstein et al [19], both of whom now use fourgland exploration on virtually all patients. Reservations have been expressed about Norman's reported outcomes [20], but they are hard to ignore, given the huge volume of cases and his experience that minimally invasive techniques have produced significantly more failures, despite his previous claims to the contrary.…”
mentioning
confidence: 99%